Mechanotransduction of Piezo1 in the cancer microenvironment: implications for NK cell-based immunotherapy - Cui, Xinmu; Zhang, Binbin; Zhao, Jianan; Tian, Huajie (Frontiers in Oncology, 2026)
Natural Killer (NK) cells serve a critical function in antitumor immunity. However, their effectiveness is often hampered by the biomechanical properties of the solid tumor microenvironment (TME), such as the stiffness of the extracellular matrix. This review focuses on the mechanosensitive ion channel Piezo1 and its role in enhancing NK cell function. Studies have shown that tumor cell stiffness, as a key physical cue, directly influences the responsiveness of NK cells. In three-dimensional (3D) matrices, the stiffening of the extracellular matrix (ECM) can activate Piezo1, leading to calcium influx that substantially boosts NK cells’ cytotoxicity and tumor infiltration ability. Remarkably, similar to Yoda1, a specific Piezo1 agonist, short-term Piezo1 activation significantly enhances NK cells’ cytotoxicity and infiltration capacity. Whether such benefits persist under prolonged stimulation without inducing functional exhaustion remains to be determined. Unlike broader review articles that discuss TME biomechanics, this study focuses on uncovering the signal transduction mechanism of the Piezo1–NK cell axis, providing new perspectives and strategies for addressing immunotherapy resistance. This mechanobiology-based framework, through detailed analysis of the Piezo1-NK cell signaling transduction mechanism, is expected to overcome bottlenecks in NK cell immunotherapy. Its application prospects are not limited to the field of oncology but can also be extended to other diseases sensitive to mechanical signals.